Factors That Influence Competitive Advantage Moderated by Digital Marketing in Small and Medium Food and Beverage Businesses in East Kalimantan - Mardiono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to examine a number of factors that can influence Competitive Advantage moderated by Digital Marketing. There are three factors that researchers believe can influence Competitive Advantages, namely Managerial Competence of Entrepreneurs, Entrepreneur Motivation, and Entrepreneurship. In the end, if a company has good Competitive Advantages, it can influence Business Performance. The objects of this study are related to the Zionist Israeli genocide against Palestine, the International Court of Justice ruling in January 2024, the history of the Israeli-Palestinian dispute, and the impacts resulting from the dispute. This type of research is a research that uses a quantitative approach. The basic reason for using quantitative research is to test the theory by collecting numerical data and then analyzing it statistically. So that quantitative research generally also involves instruments used to collect data and quantitative methods are usually related to making generalizations about the population being investigated. This study is descriptive in nature, where the data to be used is primary data through the distribution of questionnaires in order to prepare data tabulation as material for further analysis to understand and answer research questions. The research model used is to develop from a direct influence model to a direct and indirect influence between factors that influence competitive advantage with business performance and moderated by digital marketing. The population in this study is all classifications of food and beverage sector SMEs spread across East Kalimantan.